1990
DOI: 10.1016/0035-9203(90)90056-k
|View full text |Cite
|
Sign up to set email alerts
|

No need for water supplementation for exclusively breast-fed infants under hot and arid conditions

Abstract: This study was conducted in 4 villages in India during the hottest and driest season of the year to determine whether exclusively breast-fed infants need additional water under extremely hot and dry climatic conditions. The ambient temperature was 35-40 degrees C and the relative humidity 10-35%, except during the early morning hours. 63 urine samples were collected from 31 infants below 6 months of age and 28 samples from 13 infants aged 6-10 months, all of whom were receiving nothing but breast milk. Specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 10 publications
0
23
0
2
Order By: Relevance
“…Early supplementation with formula milk and other liquids was also noted in this study. It should be mentioned that breast milk alone can maintain adequate water balance in young infants and supplementary fluids are not needed even in warm climates [36,37]. …”
Section: Discussionmentioning
confidence: 99%
“…Early supplementation with formula milk and other liquids was also noted in this study. It should be mentioned that breast milk alone can maintain adequate water balance in young infants and supplementary fluids are not needed even in warm climates [36,37]. …”
Section: Discussionmentioning
confidence: 99%
“…Other reasons given by the doctors were to prevent dehydration and neonatal jaundice. Yet most babies do not need extra water, even in hot climates (Almroth & Bidinger, 1990). Further, frequent suckling is associated with a significant decrease in hyperbilinbinaemia by the sixth day of life (Yamauchi & Yamanouchi 1990).…”
Section: Discussionmentioning
confidence: 99%
“…There is no need to cleanse or prepare the gut for digestion or give extra fluids to quench thirst. Studies have shown that even in hot countries most babies do not need extra water (Almroth & Bidinger, 1990;Goldberg & Adams, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…3 Although recommendations rarely address the needs of exclusively formula-fed infants, similar recommendations for the introduction of solid or semisolid foods are generally given. 4 Breastfed infants do not require water, even in hot conditions, [11][12][13] and there is no evidence that infants consuming appropriately prepared infant formula need water either. 4 Although there is dispute in some sectors about the optimal time for the introduction of solids, there is consensus that other foods and fluids should not be introduced to either breast or formula-fed infants before 17 weeks 4 because of an increased risk of infection, [5][6][7][8] obesity, 9,10 and allergy.…”
Section: Introductionmentioning
confidence: 99%